Perencanaan Jadwal Perawatan Pencegahan Mesin Sliting Dengan Metode RCM (Realibility Centered Maintenance) Di PT. XYZ - Ahmad Rizal; Darmawan Yudhanegara; Pandena Kicky Basuki Putri (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
PT XYZ is a company engaged in manufacturing plastic packaging. In the production process, the company is used to continuously produce so that the machines must continue to operate for 3 shifts/day which will decrease engine performance and engine damage. If the lack of machine maintenance, this will result in frequent occurrence downtime which impede the course of the production process and decreased production capacity. Downtime on cutting machine (Slitting) period January 2022 – December 2022 of 9810 minutes. This research was conducted to plan treatment using the method Realibility Centered Maintenance (RCM) which aims to make recommendations for improvements to the design of repair maintenance on slitting machines. From RCM analysis on slitting machine damage to machine components according to the diagram Logic Tree Analysis and found that component time directed that is Brake Roll, LPC (Line Position Control), Slitter blades, and Touch press roll. Based on the calculation of the frequency of replacement of the unwinder components will decrease by up to 58% after the component operates for 1.75 months or 808.5 hours, the roll cylinder component will decrease by 50% after the component operates for 1.5 months or 693 hours, and the rewinder component will decrease to 66% after the component has been operating for 2 months or 924 hours. Keywords: Maintenance system, Reliability Centered Maintenance (RCM), Total Minimum Downtime (TMD)